Supplement Issue : Indonesian Acute Coronary Syndrome Summit in Conjunction with Asia Primary Angioplasty Congress (APAC) 2025 - APAC (Heart Science Journal, 2025)
This supplementary issue contains the abstracts presented at the Indonesian Acute Coronary Syndrome Summit in Conjunction with Asia Primary Angioplasty Congress (APAC) 2025 held on July 25th-26th 2025. The abstracts are grouped into three categories: Review Article, Original Article, and Case Report.